Climatology of cyclones, anticyclones and storm tracks: revision of concepts - Mendes,David; Mendes,Monica Damião (Sociedade Brasileira de Geofísica, 2004)
This paper has the finality of describe climatology of extratropical cyclones, anticyclones and storm tracks for the NH and SH. There is a long history of studies on the characteristics of synoptic systems, beginning with classical work on mid-latitude cyclones. For the SH, analyses of pressure data provide extensive statistics of the climatology of synoptic systems. Interestingly, the anticyclones mean central pressure at 38ºS in JJA and 44ºS in DJF. SH cyclones are characterized in frequency maximum in the circumpolar trough between about 50ºS and 70ºS. For the NH cyclones, the principal findings of the analysis are as follows: In January the primary maxima are in the western North Atlantic, with a peak about 45º - 50ºN, where there is a secondary peak, over the north-central Mediterranean; These characteristics are similar in April but with decrease in the frequency of centers; In July the frequencies are further reduced and the hemisphere maximum is over eastern Canada at 55ºN; The October pattern resembles that of winter, except that the Atlantic maximum is off southeast Greenland.